The Effect of Carbon Disulfide on Oxidative Injury in Vein Endothelial Cells - Chen, S.; Jian, Le; Wang, J.; Chen, Q.; Lang, H. (Zhejiang Preventive Medicine Association, 2006)
Objective: To study the toxic mechanism of atherosclerosis induced by Carbon disulfide (CS2). Methods: Human umbilical vein endothelial cells (ECV304) were cultured for 24 hours with different levels of CS2 exposure (10, 100, 1000, 10000 µmol/L and 0 µmol/L as control). Microscope was used to observe the morphological injury of endothelial cells and the method of Luminol—dependent chemiluminescence was adopted to measure the level of peroxynitrite anion of cell culture medium to observe the oxidative injury. Results: Morphological injury in endothelial cells to a different extent was observed by microscope. The level of peroxynitrite in cell culture medium with CS2 was significantly higher than that without CS2 (P < 0.05). The concentration of CS2 positively correlated with that of peroxynitrite anion(P < 0.05). Conclusions: CS2 can induce the oxidative injury in endothelial cells by producing free radicals including peroxynitrite anion.